PELATIHAN UNIT COST SEBAGAI DASAR PENETPAN TARIF BAGI BIDAN PRAKTEK SWASTA DI WILAYAH KELURAHAN PENATIH,DENPASAR - WIDARSA, WIDARSA; INDRAYATHI, P.A.; UTAMI, ARYA; SUTIARI, K.; SUARJANA, K.; MULYAWAN, HARI (Buletin Udayana Mengabdi; Vol 7 No 2 (2008): Volume 7 No.2 – September 2008, 2012)
ABSTRACT Midwifery as paramedic in a village plays an important role in primary health care in order to pursue Indonesia Sehat 2010. Midwifery should provide good services with adequate tariff for society. As one indicator of service, the use of unit cost method has become an important part in tariff calculation. It was found that knowledge of the local Midwifery about unit cost was quite low. The activity of community services was carried out at IKK-IKP department Faculty of Medicine, on 01st September 2007. This activity aimed to improve knowledge and ability of midwifery of how to use Unit Cost in tariff calculation. The method was practicing on calculate several health care services cost. The result of this activity was midwifery can create adequate tariff base on unit cost.